Rhetoric in Modern Biological Thought: A Case Study of Classical Genetics - Lilian Al-Chueyr Pereira Martins (Revista Guillermo de Ockham)
This paper mainly focuses on the book The Mechanism of Mendelian Heredity (1915) by T. H. Morgan (1866-1945), Alfred H. Sturtevant (1891-1970), Herman J. Muller (1890-1967), and Calvin B. Bridges (1889-1938). Considered by some as a landmark in genetics, it convinced specialized and not specialized at the time that the theory was established despite its crucial problems. It aims to discuss the rhetorical devices the authors used to persuade these people. The methodology comprises the analysis of primary sources, in addition to the text by Morgan et al. (1915), and secondary sources dealing with the topic, including some works by the author of this article related to the subject and its representation in science. The study concluded that Morgan et al. (1915) used their discourse, some drawings, and diagrams, unaccompanied by photographs, mainly in aspects of the theory where evidence was scarce, giving a false impression that all was clear. It is possible to find historical simplification of the facts to reinforce the authors’ arguments, lack of discussion of alternative explanations, diagrams representing ideal objects they did not observe, and theoretical examples that conflicted with the numerical data in their previous papers. In addition, they did not present problems or difficulties related to their theory. All this contributed to some problematic features of the theory not being evident and being accepted.